2013
DOI: 10.1111/1753-6405.12006
|View full text |Cite
|
Sign up to set email alerts
|

The SF‐36v2 and SF‐12v2 health surveys in New Zealand: norms, scoring coefficients and cross‐country comparisons

Abstract: Objective: To provide New Zealand population norms for version 2 of the SF-36 and SF-12 health surveys and report scoring coefficients that enable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…It has been previously described that the PCS score of the SF-12 shows impairment with age, and that HZ infection severely impacts HRQoL [ 35 , 36 ]. In addition, it has been recently showed that an episode of HZ could lead to comorbidity decompensation and could jeopardize the health status of an older person with concomitant diabetes, COPD, or cardiovascular disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously described that the PCS score of the SF-12 shows impairment with age, and that HZ infection severely impacts HRQoL [ 35 , 36 ]. In addition, it has been recently showed that an episode of HZ could lead to comorbidity decompensation and could jeopardize the health status of an older person with concomitant diabetes, COPD, or cardiovascular disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The summary scores were calculated using New Zealand population norms and US factor coefficients. 18 All outcomes were assessed at baseline, 4 weeks, and 12 weeks. Potential harms or adverse effects were recorded by asking participants about injuries, hospitalizations, or perceived adverse effects from chiropractic care during the trial.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…26 The summary scores systematically fall according to age, which also occurs in the population of other countries. [21][22][23]31,32 PCS-12 was more influenced by advances in age. This suggests that losses related to normal ageing may be more related to the physical component, which under-goes inexorable transformations over time.…”
mentioning
confidence: 99%